Integrated electronic device for detecting molecules and method of manufacture thereof - Lamagna, Alberto; Mandolesi, Pablo Sergio; Boselli, Alfredo; Lerner, Betiana; Julián, Pedro Marcelo; Pérez, Maximiliano Sebastián; Pareja Obregón, Pablo Daniel (2012)
Fil: Lamagna, Alberto. Comisión Nacional de Energía Atómica; Argentina.